2021
DOI: 10.30794/pausbed.980499
|View full text |Cite
|
Sign up to set email alerts
|

Deneti̇mli̇ Serbestli̇k Tedbi̇ri̇ Uygulanan Yükümlüleri̇n Bazi Özelli̇kleri̇ni̇n Suç Açisindan Değerlendi̇ri̇lmesi̇

Abstract: Bu çalışmanın amacı denetimli serbestlik tedbiri uygulanan yükümlülerin bazı özelliklerinin yeniden suç işleme bakışı açısından değerlendirilmesidir. Çalışma, retrospektif bir bakış açısı benimsenerek 2018 yılı ceza evinden tahliye edilenlerin TÜİK istatistikleri, Denetimli Serbestlik Daire Başkanlığı verileri ile Malatya Denetimli Serbestlik Müdürlüğünde 2018 yılında koşullu salıverilen 1153 dosyanın sosyodemografik özelliklerinin incelenmesi ile gerçekleştirilmiştir. Çalışmanın bulgularına bakıldığında yüküm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…Additionally, it has been observed that individuals who feel marginalized from society may develop an inflated sense of pride, leading to the continuation of their criminal acts. Furthermore, a study conducted revealed that individuals who have been involved in the criminal justice system exhibit an uptick in hostility toward law enforcement personnel following the commission of a crime (Porsuk, 2022). The reason why the results of this finding differ according to the literature may be the socio-demographic characteristics of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been observed that individuals who feel marginalized from society may develop an inflated sense of pride, leading to the continuation of their criminal acts. Furthermore, a study conducted revealed that individuals who have been involved in the criminal justice system exhibit an uptick in hostility toward law enforcement personnel following the commission of a crime (Porsuk, 2022). The reason why the results of this finding differ according to the literature may be the socio-demographic characteristics of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Bu kapsamda hapis cezalarına alternatif olan, suç işlemiş bireyin tekrar suç işlemesini önleyen, rehabilite edilmesini amaçlayan ve topluma uyum sağlamasını kolaylaştıran bir sistem olan denetimli serbestlik oluşturulmuştur (Kale, 2009). Günümüz ceza infaz sistemlerinin onarıcı adalet kapsamında iyileştirme ve rehabilitasyona odaklı olduğu ifade edilmektedir (Porsuk, 2022). Suç, bireye atfedilen ve öğrenilen davranış olarak tanımlanmasıyla birlikte, suçun azaltılmasında iyileştirici ve rehabilite edici yöntemler ön plana çıkmaya başlamıştır (Gün & Önder Erol, 2023).…”
Section: Introductionunclassified